Misoprostol versus Dinoprostone for induction of labour in premature rupture of membranes - R. S., Rachana; Bangal, V. B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: To compare the efficacy of misoprostol (PG E1 analog) and Dinoprostone (PGE2) for induction of labour in patients with premature rupture of membranes (PROM). Methods: This prospective study was conducted at the Department of Obstetrics and Gynaecology, Dr. BVP Rural medical college, Loni, Ahmednagar, Maharashtra. A total of 120 women (60 in each group) presenting with PROM (premature rupture of membranes) within 48 hours with gestational age between 34 weeks to 40 weeks were included. Group A women received tab misoprostol 25 mcg orally and Group B women received Dinoprostone gel vaginally kept in posterior vaginal fornix for induction of labour. Dose was repeated every 4th hourly in Group A with maximum of 4 doses and it was repeated 6th hourly In Group B with maximum of 3 doses. Results: Among 60 patients in Group A, 47 (78.33%) delivered vaginally and 13 (21.66%) were delivered by caesarean section. In Group B, 39(65%) patients delivered vaginally and 21(35%) were delivered by LSCS. Conclusions: Oral misoprostol 25 mcg 4 hourly is efficient and cost-effective alternative to PGE2 gel for cervical ripening and induction of labour in PROM patients.